Vitamin B-6 Restriction Reduces the Production of Hydrogen Sulfide and its Biomarkers by the Transsulfuration Pathway in Cultured Human Hepatoma Cells. Issue 10 (27th August 2014) - DeRatt, Barbara N.; Ralat, Maria A.; Kabil, Omer; Chi, Yueh-Yun; Banerjee, Ruma; Gregory, Jesse F.
Abstract: Background: Pyridoxal 5′-phosphate (PLP) functions as a coenzyme in many cellular processes including one-carbon metabolism and the interconversion and catabolism of amino acids. PLP-dependent enzymes, cystathionine β-synthase and cystathionine γ-lyase, function in transsulfuration but also have been implicated in the production of the endogenous gaseous signaling molecule hydrogen sulfide (H2 S) concurrent with the formation of the biomarkers lanthionine and homolanthionine. Objective: Our objective was to determine if H2 S production and concurrent biomarker production is affected by vitamin B-6 restriction in a cell culture model. Methods: We used cultured human hepatoma cells and evaluated static intracellular profiles of amino acids and in vivo kinetics of H2 S biomarker formation. Cells were cultured for 6 wk in media containing concentrations of pyridoxal that represented severe vitamin B-6 deficiency (15 nmol/L pyridoxal), marginal deficiency (56 nmol/L pyridoxal), adequacy (210 nmol/L pyridoxal), and standard medium formulation providing a supraphysiologic pyridoxal concentration (1800 nmol/L pyridoxal). Results: Intracellular concentrations of lanthionine and homolanthionine in cells cultured at 15 nmol/L pyridoxal were 50% lower ( P < 0.002) and 47% lower ( P < 0.0255), respectively, than observed in cells cultured at 1800 nmol/L pyridoxal. Extracellular homocysteine and cysteine were 58% and 46% higher, respectively, in severely deficient cells than in adequate cells ( P < 0.002). Fractional synthesis rates of lanthionine ( P < 0.01) and homolanthionine ( P < 0.006) were lower at 15 and 56 nmol/L pyridoxal than at both higher pyridoxal concentrations. The rate of homocysteine remethylation and the fractional rate of homocysteine production from methionine were not affected by vitamin B-6 restriction. In vitro studies of cell lysates using direct measurement of H2 S also had a reduced extent of H2 S production in the 2 lower vitamin B-6 conditions. Conclusion: In view of the physiologic roles of H2 S, these results suggest a mechanism that may be involved in the association between human vitamin B-6 inadequacy and its effects on human health.